8‐Oxo‐7, 8‐dihydroguanine and uric acid as efficient predictors of survival in colon cancer patients. Issue 2 (5th August 2013) - Dziaman, Tomasz; Banaszkiewicz, Zbigniew; Roszkowski, Krzysztof; Gackowski, Daniel; Wisniewska, Ewa; Rozalski, Rafał; Foksinski, Marek; Siomek, Agnieszka; Speina, Elzbieta; Winczura, Alicja; Marszalek, Andrzej; Tudek, Barbara; et al.
Abstract : The aim of this work was to answer the question whether the broad range of parameters which describe oxidative stress and oxidatively damaged DNA and repair are appropriate prognosis factors of colon cancer (CRC) patients survival? The following parameters were analyzed for 89 CRC patients: concentration of uric acid and vitamins A, E, C in plasma; levels of 8‐oxodGuo (8‐oxo‐7, 8‐dihydro‐2′‐deoxyguanosine) in DNA of leukocyte and colon tissues; urinary excretion rates of 8‐oxodGuo and 8‐oxoGua (8‐oxo‐7, 8‐dihydroguanine); the activity and mRNA or protein level of repair enzymes OGG1, APE1, ANPG, TDG and PARP1. All DNA modifications and plasma antioxidants were analyzed using high performance liquid chromatography (HPLC) or HPLC/gas chromatography‐mass spectrometry techniques. Expression of repair proteins was analyzed by QPCR, Western or immunohistochemistry methods. Longer survival coincided with low levels of 8‐oxodGuo/8oxoGua in urine and 8‐oxodGuo in DNA as well as with high concentration of uric acid plasma level. In contrast to expectations, longer survival coincided with lower mRNA level in normal colon tissue of the main 8‐oxoGua DNA glycosylase, OGG1, but no association was found for PARP‐1 expression. When analyzing simultaneously two parameters the discriminating power increased significantly. Combination of low level of urinary 8‐oxoGua together with low level of 8‐oxodGuo in leukocyte (both below median value) or high concentration of plasma uric acid (above median value) have the best prediction power. Since prediction value of these parameters seems to be comparable to conventional staging procedure, they could possibly be used as markers to predict clinical success in CRC treatment. Abstract : What's new? Many patients with colon carcinoma experience recurrence of the cancer after treatment and it remains unclear how to properly predict treatment success. Here, the authors used a combinatorial approach to search for biomarkers that correlate with survival. They found that a combination of low levels of urinary 8‐oxo‐7, 8‐dihydroguanine either with low levels of 8‐oxo‐7, 8‐dihydro‐2'‐deoxyguanosine in leukocyte DNA or with high levels of uric acid in blood plasma had significant predictive power for the prognosis of colorectal cancer, comparable to conventional staging procedures. Both combinations represent markers of the oxidative stress/DNA damage pathway, which in combination with clinical staging may be used to identify high‐risk groups of patients to improve personalized treatment options.